Edukasi dan Pendampingan Penerapan Perilaku “BORIA” dalam Upaya Penurunan Kejadian Diabetes Melitus di Desa Genaharjo Kec. Semanding Kab. Tuban - Nur Cahyani, Nabila; Puspitadewi, Teresia Retna; Cahyani, Mirna Tri; Nurjanah, Noviatul; Azaro, Devia Fatimatus; Irianti, Dhevina Yogi Ara (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Nusa Utara, 2025)
In the era of globalization, which is where there is a global era, there is a shift from infectious diseases to non-communicable diseases such as the emergence of more and more degenerative diseases, one of which is Diabetes Mellitus (DM). Diabetes mellitus is one of the diseases that are most suffered by the Indonesian people. This disease is called a silent killer because patients are often unaware so they are prone to complications Diabetes mellitus has the main cause, namely an unhealthy lifestyle. On the other hand, the people of Genaharjo Village, Semanding District, Tuban Regency have a habit of drinking coffee, staying up late, and among others obesity. This is the basis for the implementation of the student creativity program by providing an overview and explanation related to diabetes mellitus, the implementation of healthy living behaviors with the